The influence of religiosity and quality of work life on employee job satisfaction on ministry religion affairs of Kolaka Regency - Hamzah, Akbar; Ismanto, Ismanto; stiadi, Muhamad (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
Currently, there are still many employees who do not feel satisfied with carrying out their work. However, in the results of preliminary observations that have been made at the Kolaka Regency Ministry of Religious Affairs Office, it was found that employees feel high job satisfaction, which the researcher then identified as being caused by religiosity and the quality of work life that employees feel. This quantitative study aims to determine whether there is an influence of religiosity and quality of work life on employee job satisfaction. This study involved 41 employees who are civil servants (PNS) and were positioned as respondents. The researcher used observation and questionnaires to answer the two research objectives. This study found that (1) there is a significant positive influence between religiosity and employee job satisfaction, and (2) there is a significant positive influence between quality of work life and employee job satisfaction. Finally, this study provides policy recommendations for the Kolaka Regency Office of the Ministry of Religious Affairs in the future, which is still very important and relevant to maintaining and improving the religiosity and quality of work life of employees.